Gross Anatomical Studies on Primary Lymphoid Organs (Thymus and Bursa of Fabricius) of Kadaknath Birds - Kanasiya, SA; Kamore, SK; Bahariya, RK; Gupta, SK; Jatav, GP (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The gross anatomical study of thymus and bursa of Fabricius was carried out on 30 Kadaknath birds of different age groups ranging from day old to 26 week. The birds were divided into five equal groups according to age as day old to 2 week, 2 to 4 weeks, 4 to 8 weeks, 8 to 16 weeks and 16 to 26 weeks, each consisted of six birds. The shape, colour and location were observed. The thymus gland in Kadaknath consisted of two long chains having 6-8 irregular shaped lobes. The shape and color of thymic lobes as well as length and width of thymus varied amongst groups. Grossly there was no regression of thymus after 26th week of age. The bursa of Fabricius was located on the dorsal wall of proctodeum of cloaca. The shape and color of bursa of Fabricius varied amongst age groups. Grossly there was complete regression of bursa after 25th week of age. The dissimilarities in these findings might be due to species difference.